Pengembangan Produk Pangan Lokal yang Berpotensi untuk Penurunan Stunting di Kabupaten Pemalang - Santoso Nugroho (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2023)
ABSTRACT Background: Stunting is a serious problem in Indonesia that must be addressed immediately. The main cause of stunting is due to the lack of public nutrition, especially in couples of childbearing age and childhood. Even though Indonesia is rich with a variety of local food sources, it is necessary to innovate in making food that has high nutritional value by utilizing existing local food sources. The purpose of this Community Service is to identify local food sources that are widely available in the village of Surajaya, formulate food products to increase their nutritional value based on local wisdom, and assist the community in manufacturing, packaging and labeling. The methods used are Focus Group Discussions, demonstrations, and mentoring. Result: A new food product has been made, namely cassava nuggets enriched with Moringa leaves. Conclusion: cassava as a local food source can be used as a new food product that is rich in nutrients and can be used as an alternative stunting prevention food that is in demand by the public.